Preparation and characterization of nanostructure high efficient CdS/Si hetrojunction by CBD - Mousa, Ali M. (Iraqi Journal of Physics, 2009)
In this paper, CdS/Si hetrojunction solar cell has been made by Chemical Bath Deposition (CBD) of CdS thin film on to monocrystalline silicon substrate. XRD measurements approved that CdS film is changing the structure of CdS films from mixed hexagonal and cubic phase to the hexagonal phase with [101] predominant orientation. I-V characterization of the hetrojunction shows good rectification, with high spectral responsivity of 0.41 A/W, quantum efficiency 90%,and specific detectivity 2.9*1014 cmHz1/2W -1 .